PELATIHAN PENERAPAN AKUNTANSI BERBASIS SAK-ETAP UNTUK MENINGKATKAN KINERJA KEUANGAN PADA UMKM PEMPEK DAPOER MAMISU PALEMBANG - Putri Triyana Kharisma; Yeni Widyanti (Abdi Jurnal Publikasi, 2025)
The purpose of this study is to determine that an MSME must implement an accounting recording system based on SAK ETAP. The implementation of Non-Public Accountability Entity Accounting Standards (SAK ETAP) is very important for Micro, Small, and Medium Enterprises (MSMEs) in improving the quality of financial reporting. The purpose of this training is to provide skills to small and medium enterprises in preparing financial reports according to SAK ETAP which can be used to analyze financial performance and facilitate financing. The results of the training showed an increase in participants' understanding of SAK ETAP-based accounting and its impact on business decision making.